Self-esteem and cannabis use in adolescents: An integrative review - Medina-Quevedo, Pablo; Guzmán-Ortiz, Elizabeth; Álvarez-Aguirre, Alicia; Martín del campo-Navarro, Alicia Sarahy; García-Campos, María de Lourdes (Horizonte Sanitario, 2023)
Objective: to identify the scientific evidence related to the influence of self-esteem on adolescent cannabis use.Materials and method: during the period of february-april 2022, an integrative review of the scientific literature published in the last ten years (2012-2022) was carried out. The six-step methodology proposed by Toronto and Remington was used in the BVS, PubMed, TRIP and Dialnet search engines, as well as in the Redalyc, Cochrane, EBSCOhost, Web of Science and CUIDEN databases. A total of 1,491 articles were found, when applying inclusion and elimination criteria, a total of ten quantitative studies were considered in the final sample.Results: it was found that adolescents with low self-esteem are prone to influences that encourage the initiation of cannabis use. When considered as a positive attitude of the person towards himself, it favors the feeling of security and regulates behavior through a process of self-evaluation, so that it enables adolescents to adapt to their environment. In this sense, three main categories were observed: moderator variable in cannabis use; predictor variable of cannabis use; and intervention component.Conclusions: the protective and predictive role of self-esteem for cannabis use in adolescents was demonstrated, likewise, early detection and interventions aimed at improving skills for the regulation of emotions influenced by cognitive factors are effective in the promotion and prevention of cannabis use in adolescents. Keywords: Self-esteem; Cannabis; Adolescent; Nursing; Mexico.